Democratic elitism new theoretical and comparative perspectives - edited by Heinrich Best (Boston Brill, 2011)
This book reconsiders Joseph Schumpeter's democratic elitism in light of the directions that recent theories of democracy have taken, and it analyzes democratic elitism's workings in western and eastern European states early in the 21st century.
Includes bibliographical references and index.
Keywords: Democracy--Congresses.